Business Process Reengineering in Water Billing Administration: A Case Study of KPAB Gang Gedang Mas - Devi Aprilianti; Wildan Suharso (Universitas Islam Indragiri, 2026)
The water billing administration process in Gang Gedang Mas, Curungrejo Village, is still conducted manually, resulting in slow procedures, inefficiency, and a high risk of errors. This study aims to improve the efficiency and accuracy of the water billing administration process through a Business Process Reengineering (BPR) approach. The improvements focus on four main processes: water meter recording, data entry, bill calculation, and billing information distribution, involving two key actors: field officers and administrative staff. This research employed a case study method, consisting of direct observation, process modeling using BPMN notation, and the measurement of processing time efficiency and throughput within one billing cycle before and after the process redesign. The proposed solution is a digital process model design that supports workflow automation at the design level, without implementing an actual system, while still maintaining the operational role of field officers. The results indicate a significant reduction in processing time, from 684 minutes to 168 minutes, along with a 307.5% increase in administrative process throughput efficiency within one billing cycle. This study demonstrates that applying BPR through process model redesign can optimize water billing management in small-scale communities with limited infrastructure, providing an efficient solution that can be adapted to similar contexts.